2003
DOI: 10.1117/12.508655
|View full text |Cite
|
Sign up to set email alerts
|

Composite filters for search time reduction for 3D model based object recognition

Abstract: This paper investigates the role of composite filters in reducing the search time for 3D model based object recognition. When one moves from 2D to 3D, one is faced with a huge amount of information to deal with. The composite filter combined with a multistage scheme is developed for processing this huge information. The design scheme for the composite filters is also elaborated. The procedures discussed in this paper demonstrate how detection of these various model images might help formulate a new metric for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…We should notice that this conclusion is similar to that noted by Mohammed et al in [32]. The low performances of the binarized POF is confirmed by a comparison between the results obtained by Mohammed et al [32] and those reported by Rahman et al [31].…”
Section: Composite Filters Used For Comparison With the Aspofsupporting
confidence: 91%
See 1 more Smart Citation
“…We should notice that this conclusion is similar to that noted by Mohammed et al in [32]. The low performances of the binarized POF is confirmed by a comparison between the results obtained by Mohammed et al [32] and those reported by Rahman et al [31].…”
Section: Composite Filters Used For Comparison With the Aspofsupporting
confidence: 91%
“…It is important to point out that the PCE values obtained from the correlation of the letter V correlated with the same filters have an average value less than 10 -3 , and support the conclusions reported in [31].…”
Section: Composite Filters Used For Comparison With the Aspofsupporting
confidence: 84%
“…One of the characteristics of the KDP back-reflection image is the presence of well-defined, relatively stable fringe patterns within the beam. We show in this paper that these fringe patterns facilitate a stable beam position detection method based on a composite [2] amplitude modulated phase only matched filter (AMPOF) [3].…”
Section: Introductionmentioning
confidence: 92%
“…Moving to an AMPOF performed further optimization on the composite CMF. Optimization was improved even further by developing a composite AMPOF filter [2,3] producing a radial standard deviation of only 0.27 pixels.…”
Section: Algorithm Testing and Modificationsmentioning
confidence: 99%
“…The National Ignition Facility, currently under construction at the Lawrence Livermore National Laboratory, is a stadium-sized facility containing a 192-beam, 1.8-megajoule, 500-terawatt, ultraviolet laser system for the study of inertial confinement fusion and the physics of matter at extreme energy densities and pressures [1] . The FOA is the last element of the NIF main laser system and the first of the target area systems.…”
Section: Introductionmentioning
confidence: 99%